(untitled) (Baghdad Science Journal, 2024)
Diabetes mellitus caused by insulin resistance is prompted by obesity. Neuropeptide Nesfatin-1 was identified in several organs, including the central nervous system and pancreatic islet cells. Nesfatin-1 peptide appears to be involved in hypothalamic circuits that energy homeostasis and control food intake. Adiponectin is a plasma collagen-like protein produced by adipocytes that have been linked to the development of insulin resistance (IR), diabetes mellitus type 2 (DMT2), and cardiovascular disease (CVD). Resistin was first identified as an adipose tissue–specific hormone that was linked to obesity and diabetes. The aim of this study was to estimate the relationship between human serum nesfatin-1, adiponectin, resistin concentration, and obesity with T2DM. The results show a significant increase in serum neisfatin-1 and resistin levels in the obese diabetic group compared to the non-obese diabetic group. Adiponectin levels had a highly significant decrease in the obese diabetic group compared to the non-obese group and obese control group. Serum Nesfatin-1 and some variables, there was a significant positive correlation with (BMI, insulin, HOMA-IR), and serum resistin had a significant positive correlation with (BMI, WC, TG, insulin, HOMA-IR).On the other hand, there was a negative correlation between serum adiponectin and (BMI, TG, and HOMA-IR). The present results suggest that nesftin-1 may have a role in controlling food intake as well as the development of IR in obese patients.